Faktor Faktor yang Mempengaruhi Produksi Tanaman Tomat (Solanum Lycopersicum): (Di Kelurahan Kota Besi Hulu Kecamatan Kota Besi Kabupaten Kotawaringin Timur) - Mahesti Mahesti; Ekamonika Manihuruk (Flora : Jurnal Kajian Ilmu Pertanian dan Perkebunan, 2026)
This research was conducted in April 2024 in Kota Besi Hulu Village, Kota Besi Subdistrict, Kotawaringin Timur Regency. The research location was determined purposively. The objectives of this study were: (1) to analyze the characteristics of tomato farmers in Kota Besi Hulu Village, Kota Besi Subdistrict, Kotawaringin Timur Regency; and (2) to analyze the factors influencing tomato production in the same area. The sampling technique employed was a census (saturated sampling), in which all active tomato farmers who were members of farmer groups in Kota Besi Hulu Village were included as respondents. A total of 64 tomato farmers participated in this study. The data collected were analyzed using the Cobb–Douglas production function model. The results of the study in Kota Besi Hulu Village, Kota Besi Subdistrict, Kotawaringin Timur Regency, indicate important patterns in local farming practices based on data regarding land area, fertilizer use, seed use, pesticide use, and tomato production. The majority of farmers cultivated land ranging from 7,060.12 to 7,614.72 hectares, reflecting a tendency to manage relatively large farm areas. In terms of fertilizer application, most farmers used between 130.05 and 139.53 kilograms, suggesting a preference for higher input levels to achieve optimal yields. Regarding seed use, the dominant range was between 156.04 and 175.36 kilograms, which may contribute to better production outcomes. Pesticide application also showed a dominant pattern within the range of 4,001.72 to 4,878.76 liters, indicating farmers’ primary strategy in controlling pests and diseases.